Sanitasi dan Higienitas Tempat Pelelangan Ikan Serta Analisis Mutu Organoleptik Ikan Tongkol Lisong (Auxis rochei Risso, 1810) di Muara Angke, Jakarta Utara - Tiaraningsih, Thania; Pratama, Rusky Intan; Mulyani, Yuniar; Rostini, Iis (Jurnal Perikanan Unram, 2025)
The Fish Auction Place (FAP) is a facility that supports fishermen in distributing their catches. Muara Angke FAP is one of the active auction places in Jakarta. Fish is a perishable commodity that requires proper handling to maintain its quality, including hygiene and sanitation facilities, especially to preserve the quality of little tuna (Auxis rochei). This study aims to analyze the sanitation and hygiene conditions at Muara Angke FAP based on Minister of Marine Affairs and Fisheries Decree No. 1 of 2007 (KEP. KP 01/MEN/2007), assess the organoleptic quality of little tuna, and analyze the relationship between sanitation-hygiene and tuna quality. The research was conducted from January to February 2025 using a case study method. Sanitation and hygiene data were obtained using purposive sampling, while little tuna samples for organoleptic and pH tests were taken using simple random sampling. Spearman correlation was used to analyze the relationship between FAP sanitation-hygiene and tuna quality. The results show that most sanitation and hygiene aspects meet the standards, although some deficiencies remain in facilities such as handwashing stations, toilets, environmental cleanliness, and warning signs. The organoleptic test yielded a final score of 7, indicating that frozen little tuna at Muara Angke FAP is still considered fresh. The pH ranged from 5.3 to 5.7, also indicating freshness. Spearman correlation analysis showed a weak positive relationship (r= 0.281) with no significant correlation (p= 0.231) between sanitation-hygiene and the quality of little tuna.